Influência da variação no uso das soluções de preservação na não-função primária do enxerto hepático: contribuição ao estudo da transplantação de fígado no Pará - SANTOS JUNIOR, Antônio João de Oliveira (2023)
INTRODUCTION: Due logistic difficulties in Brazil, the organ harvesting and allocation of these, caught in distant cities from transplantation centers, the use of cold storage solutions that allow the increasing of cold preservation time without causing damages to the functionality of graft is extremely important for the success of Transplantation process. AIM: The objective of this research is to evaluate the relationship between cold storage solutions and primary nonfunction in liver grafts caught in Pará and used for transplantation in Brazil. METHOD: This is a prospective cohort study, of 23 handbooks of cadaveric liver donors, in the Ophir Loyola Hospital, in Belém-Pará, in which were analyzed the relationship between the variation of cold storage solutions and primary nonfunction. RESULTS: From December 4th of 2004 through August 12th of 2007, 23 liver grafts harvesting were performed. 14 (60.87%) donors were male and 9 (39.13%) female. In 17 (73,91%) cases, the cold storage solution used for portal perfusion was: 1 liter of Eurocollins and 1L of Belzer solution; and in the 6 remaining donors other associations were used. For aortic perfusion, we observed that in 7 (31.82%) donors were used the association of 2 liters of Eurocollins; in 6 (27.27%) cases, 1 liter of Eurocollins and 1 liter of Belzer; in 3 (13.64%) cases, 2 liters of Belzer; in 2 (9%) donors, 3 liters of Eurocollins and in the 4 remaining donors other associations were used. Primary nonfunction of the liver did not occur. CONCLUSION: Although the great variability in the used cold storage solutions, we do not observe correlation with the existence of primary nonfunction.